The development of universal alopecia during therapy with TNF-α inhibitors in patients with ankylosing spondylitis: description of three cases - M. V. Kireeva; E. M. Agafonova; A. E. Dimitreva; K. V. Sakharova; S. O. Krasnenko; Sh. F. Erdes (Научно-практическая ревматология)
Alopecia areata (АA) is an autoimmune multifactorial disease characterized by increased hair loss as a result of morphological and functional changes in hair follicles. АA is divided into four main forms, among which the most severe is the universal form (UA), in which complete hair loss is possible throughout the body. Alopecia in the practice of a rheumatologist can occur with some systemic diseases of the connective tissue, with the use of high doses of chemotherapy drugs and, more recently, with the use of inhibitors of tumor necrosis factors alpha (TNF-α). The article presents 3 clinical cases of the development of UA during therapy with TNF-α. Possible mechanisms are discussed, as well as the role of pro-inflammatory cytokines in the development of this condition.